Boosting Vocabulary Mastery Through TED Talks Video: Students’ Perceptions and Challenges - Anggoro Jati, Tri; Karim, Sayit Abdul; Matas, Gordan (Acitya: Journal of Teaching and Education, 2025)
Audio-visual content has emerged in the current digital era as a powerful tool for enhancing students’ vocabulary mastery. This study explores the perceptions and challenges students encounter when using TED Talks as a medium of learning English vocabulary. Employing a qualitative research design, this study collected the data through open-ended questions. Fifteen students in the third-grade XII of MAN 2 Yogyakarta participated as the respondents. The data was qualitatively analysed by explaining every respondent's answers based on each theme. Furthermore, the respondents ‘answers were analysed using the interactive model theory proposed by Miles and Huberman (1994). The finding revealed that students perceived positive view on the TED Talks video by appreciating their engaging content and authentic language exposure available. However, several challenges were identified including difficulties in understanding various accents, the fast pace of some talks, and the complexity of specific vocabulary. Despite these obstacles, students found strategies to overcome these challenges such as repeated viewing of videos, using subtitles, and additional vocabulary practice. This study inferred that TED Talks can be a valuable resource for enhancing learning vocabulary, and provides adequate support and supplementary learning materials for learners. This study offers insights for educators on effectively integrating TED Talks video into classroom practice, and language curricula, and suggests directions for future similar studies.